High-entropy alloy coating with hydrogen evolution and oxygen evolution dual-catalytic performance and preparation method and application of high-entropy alloy coating
The preparation of FeCoCrNiAlCu high-entropy alloy coating through plasma spraying technology solves the problems of kinetic slowness in existing electrocatalysts in HER and high cost of precious metal catalysts, and achieves excellent bifunctional catalytic performance under acidic conditions, and has cost-effective application potential for electrochemical water decomposition.
Patent Information
- Application Number
- CN202411950727.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing electrocatalysts are slow in cathode hydrogen evolution reaction (HER), and precious metal catalysts are costly and scarce, making it difficult to achieve cost-effective electrochemical water decomposition.
The FeCoCrNiAlCu high-entropy alloy coating was prepared by plasma spraying technology, and the alloy powder was processed through a vacuum air atomization device to form a coating with hydrogen evolution and oxygen evolution dual catalytic properties.
The FeCoCrNiAlCu HEA coating with excellent bifunctional catalytic capability under acidic conditions was achieved, exhibiting good hydrogen evolution (HER) and oxygen evolution (OER) catalytic properties, with a small overpotential and a low Tafel slope.
Smart Images

Figure CN119710793A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrocatalysts, and in particular to a high entropy alloy coating with dual catalytic performances of hydrogen and oxygen evolution, and a preparation method and application thereof. Background Art
[0002] In the process of global transformation from traditional energy to clean energy, hydrogen energy is considered to be an important clean energy because of its high energy density, sustainability and pollution-free combustion. Electrochemical water splitting to produce hydrogen through the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER) is a promising way to convert solar energy, water and wind energy into chemical energy, because no pollutants are produced during the reaction, which is conducive to achieving the goal of carbon peak. However, the sluggish kinetics of the cathode hydrogen evolution reaction (HER) leads to excessively high potentials in practical applications. Although noble metals such as Pt, Ir, Ru and their compounds have low overpotentials and good reaction kinetics in practical applications, their high cost and resource scarcity limit their widespread industrial application. Therefore, it is crucial to develop electrocatalysts with high economic benefits and excellent catalytic activity. According to the "volcano plot" that the activity of HER catalysts first rises and then falls with the change of MH bond strength, the optimized catalyst based on low-cost transition metals should have an MH bond strength comparable to that of platinum. In past studies, cheap and abundant 3d transition metals (TM) such as Fe, Co, Ni and their compounds have been widely used in the field of electrocatalysis.
[0003] However, under acidic reaction conditions, the stability and catalytic performance of 3d transition metals are poor. The development of efficient and stable transition alloys is the key to promoting the development and practical application of electrochemical cracking technology. HEAs composed of five or more different atoms with a content of 5%-35% have attracted the attention of many researchers due to their unique high entropy effect, lattice distortion effect, cocktail effect, and hysteresis diffusion effect. According to the four unique effects of high entropy alloys and the wide adsorption energy intensity generated by the random arrangement of surface atoms, they have become potential materials for various catalytic reactions. Among them, the severe lattice distortion effect and hysteresis diffusion effect caused by different atomic sizes greatly promote the corrosion resistance of high entropy alloys under acidic and alkaline conditions. Aimi et al., the nine-element self-reconstructed high entropy alloy prepared by smelting and crushing showed excellent oxygen evolution reaction (OER) stability under acidic conditions. Frank et al. prepared CoCrFeNi equimolar high entropy alloys by arc melting and showed good stability and hydrogen evolution reaction (HER) performance under acidic conditions. Liu et al. prepared nanoporous NiMnFeMo materials by dealloying method and showed excellent water splitting activity under alkaline conditions. Among various preparation methods, HEAs prepared by plasma spraying have been extensively studied due to their low material consumption, excellent bonding strength, good wear resistance and corrosion resistance, but their use as electrocatalysts is still in the exploratory stage. The formation of holes in the coating during plasma spraying due to its process characteristics is conducive to increasing the specific surface area of the reaction and exposing more reactive sites. The metal oxides produced during the spraying process change the metal electron configuration and may further promote the occurrence of the reaction. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high entropy alloy coating with dual catalytic performance of hydrogen evolution and oxygen evolution, and a preparation method and application thereof.
[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0006] One of the purposes of the present invention is to provide a method for preparing a high entropy alloy coating having dual catalytic performance of hydrogen evolution and oxygen evolution, comprising the following steps:
[0007] S1. Take Fe, Co, Cr, Ni, Al and Cu single metals with a purity higher than 99.9% in a molar ratio of 1:1:1:1:1:1, clean and remove oil and impurities on the surface of each metal raw material, rinse with alcohol and blow dry for later use;
[0008] S2, placing the metal raw materials into an electric arc furnace to melt into a FeCoCrNiAlCu high entropy alloy;
[0009] S3, using a vacuum gas atomization device to process the FeCoCrNiAlCu high entropy alloy into FeCoCrNiAlCu high entropy alloy powder for spraying;
[0010] S4. Clean the substrate surface before spraying and perform sandblasting on the substrate surface to increase the surface roughness of the substrate;
[0011] S5. Use plasma spraying equipment to spray FeCoCrNiAlCu high entropy alloy powder on the surface of the substrate to prepare HEA coating. The main parameters of the spraying are: working voltage: 42V, working current: 600A, and argon gas flow rate 45L / min.
[0012] Furthermore, the main parameters of the vacuum gas atomization device are: gas atomization is 5.0MPa, heating power is 30kW, feed speed is 0.05mm / s, and alloy powder with a particle size of 14-45μm is sieved for spraying.
[0013] Preferably, the substrate is Q235 steel plate.
[0014] Preferably, the blasting material used in the sandblasting process is white corundum Al2O3.
[0015] Preferably, the spraying thickness of the HEA coating is 400 μm.
[0016] The second object of the present invention is to provide a high entropy alloy coating prepared by the above method and having dual catalytic properties of hydrogen evolution and oxygen evolution.
[0017] The third object of the present invention is to provide a high entropy alloy coating with dual catalytic performance of hydrogen and oxygen evolution for use as a dual catalyst for hydrogen and oxygen evolution in water electrolysis.
[0018] Compared with the prior art, the present invention successfully prepared the FeCoCrNiAlCu HEA coating and used it in water electrolysis technology under acidic conditions; the experimental results show that the FeCoCrNiAlCu HEA coating has excellent bifunctional catalytic ability and exhibits good hydrogen evolution (HER) and oxygen evolution (OER) catalytic performance in 0.5MH2SO4 electrolyte. The presence of pores in the coating is a key factor in exposing active sites, and metal oxides further promote the reaction; and the synergistic effect of multiple elements in HEA enables the coating to have good catalytic performance, showing a small cross point and Tafel slope and good reaction stability; the present invention not only provides a new strategy for the preparation of non-precious metal HEA catalysts, but also provides an effective method for the practical application of high-efficiency HEA electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1Structural characterization of the FeCoCrNiAlCu HEA coating prepared in accordance with an embodiment of the present invention: (a) FeCoCrNiAlCu high entropy alloy powder; (b) XRD spectrum; (c) SEM image of the FeCoCrNiAlCu HEA coating; (d) SEM image and energy spectrum of the FeCoCrNiAlCu HEA coating.
[0020] Figure 2 XPS spectra of the FeCoCrNiAlCu HEA coating and bulk FeCoCrNiAlCu high entropy alloy prepared according to the embodiments of the present invention: (a) iron 2p orbital; (b) cobalt 2p orbital; (c) chromium 2p orbital; (d) nickel 2p orbital; (e) aluminum 2p orbital; (f) copper 2p orbital.
[0021] Figure 3 OER test performance of the FeCoCrNiAlCu HEA coating prepared according to the embodiment of the present invention: (a) LSV curve of oxygen evolution reaction; (b) Tafel plot; (c) double layer capacitance of oxygen evolution reaction.
[0022] Figure 4 HER test performance of the FeCoCrNiAlCu HEA coating prepared in accordance with an embodiment of the present invention: (a) LSV curve of hydrogen evolution reaction; (b) Tafel plot; (c) double layer capacitance of hydrogen evolution reaction; (d) Nyquist plot; (e) stability test of hydrogen evolution reaction; (f) LSV curve of overall water decomposition.
[0023] Figure 5 The following are scanning electron microscope images, energy spectrum and XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling according to the embodiment of the present invention: (a) scanning electron microscope image of the FeCoCrNiAlCu HEA coating after cycling; (b) iron 2p. orbital XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling; (c) cobalt 2p. orbital XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling; (d) chromium 2p. orbital XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling; (e) nickel 2p. orbital XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling; (f) aluminum 2p. orbital XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling; (g) copper 2p. orbital XPS spectrum of the FeCoCrNiAlCu HEA coating after cycling. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0025] S1. Take Fe, Co, Cr, Ni, Al and Cu single metals with a purity higher than 99.9% in a molar ratio of 1:1:1:1:1:1, clean and remove oil and impurities on the surface of each metal raw material, rinse with alcohol and blow dry for later use;
[0026] S2, placing the metal raw materials into an electric arc furnace to melt into a FeCoCrNiAlCu high entropy alloy;
[0027] S3, using a vacuum gas atomization device to process the FeCoCrNiAlCu high entropy alloy into FeCoCrNiAlCu high entropy alloy powder for spraying, the main parameters of the vacuum gas atomization device are: gas atomization is 5.0MPa, heating power is 30kW, feeding speed is 0.05mm / s, and alloy powder with a particle size of 14-45μm is sieved for spraying;
[0028] S4, using Q235 steel plate as the substrate, cleaning the substrate surface before spraying, and sandblasting the substrate surface to increase the surface roughness of the substrate, the sandblasting material is white corundum Al2O3;
[0029] S5. Use Praxair3710 plasma spraying equipment to spray FeCoCrNiAlCu high entropy alloy powder on the surface of the substrate to obtain FeCoCrNiAlCu HEA coating. The main parameters of spraying are: working voltage: 42V, working current: 600A, argon flow rate 45L / min, and the spraying thickness of FeCoCrNiAlCu HEA coating is 400μm.
[0030] The FeCoCrNiAlCu HEA coating was cut into 10 mm × 5 mm × 2 mm pieces using a DK7720 cutting machine, and the workpiece and the wire were encapsulated with epoxy resin for subsequent electrochemical testing.
[0031] Comparative Example 1
[0032] The difference from Example 1 is that FeCoCrNiCu high entropy alloy is used.
[0033] Comparative Example 2
[0034] The difference from Example 1 is that FeCoCrNiAl high entropy alloy is used.
[0035] The high entropy alloy and HEA coating of Example 1, Comparative Example 1 and Comparative Example 2 were respectively taken for material characterization
[0036] The morphology and structure of the samples were characterized by scanning electron microscopy (Gemini 300), X-ray diffractometer (Shimadzu-7000) with a scanning angle of 20°-80°, X-ray photoelectron spectroscopy (XPS, Thermo Science K-Alpha), and transmission electron microscopy (JEM2100). The coating surface was polished with sandpaper of different grits and polished with diamond polishing paste 20000# to prepare a surface suitable for observation.
[0037] The structural characterization results of the prepared FeCoCrNiAlCu HEA coating are shown in Figure 1 As shown: (a) FeCoCrNiAlCu high entropy alloy powder; (b) XRD pattern; (c) SEM image of FeCoCrNiAlCu HEA coating; (d) SEM image and energy spectrum of FeCoCrNiAlCu HEA coating. Figure 1 As can be seen from (a) in the cast FeCoCrNiAlCu HEA, the Cu element segregates in the alloy due to its large electronegativity, while the other elements are evenly distributed. Figure 1 As shown in (a), the powder surface has good formability and is a regular round shape without obvious defects. Under macroscopic EDS, the element distribution is uniform and there is no segregation. The morphology and element distribution of the remaining high entropy alloy powder are shown in Figure 1 As shown in (b) and (c) in Figure 2, high entropy alloy coating was prepared on Q235 substrate by plasma spraying technology. Figure 1 The X-ray diffraction patterns of FeCoCrNiAlCu HEA and FeCoCrNiAlCu HEA coatings shown in (b) show that the diffraction peaks of the coating and the cast state are similar, indicating that the diffraction peak distribution has not changed significantly after spraying. The strong (111) and (200) diffraction peaks are located at 2θ=43.494° and 50.673°, indicating that the coating and the HEA alloy body are face-centered cubic structures. The (021) diffraction peak of the coating is located at 2θ=37.239°, which is a metal oxide diffraction peak (PDF#89-3080). The X-ray diffraction patterns of the remaining components are shown in Figure 1. Figure 1 The junction between the coating and the substrate is shown in (b). Figure 1 As shown in (c), the bonding between the coating and the substrate is a micro-area metallurgical bonding with good bonding strength, and it is not easy to peel off during the catalytic reaction process. The morphology of the bonding between the FeCoCrNiAl, FeCoCrNiCu HEA coating and the FeCoCrNiAlCuHEA coating is similar. Figure 1In (d), the coating morphology is a standard river-like pattern, which is a typical morphology of thermal spraying. This is because the powder melts rapidly during the spraying process, and some unmelted particles and molten droplets quickly collide with the substrate surface layer by layer to form a layered stacking structure. The distribution of Cu and Al elements in the coating element distribution is inconsistent with the distribution of other elements. This may be due to the difference in electronegativity of different elements during the spraying process and the different degrees of reactivity in the air. The segregation of Cu elements can increase the conductivity of the coating during the reaction process. In addition, the presence of metal oxides can be observed in the prepared coating elements. Due to the high temperature of the plasma jet, the metal is inevitably oxidized in the atmospheric environment even with argon protection. Among them, Al has a high degree of overlap with oxygen in element distribution due to its high activity.
[0038] In order to study the valence state of the metal elements in the coating, the as-cast FeCoCrNiAlCu HEA and the FeCoCrNiAlCu HEA coating were compared by X-ray photoelectron spectroscopy (XPS). The XPS spectra of the prepared FeCoCrNiAlCu HEA coating and the bulk FeCoCrNiAlCu high entropy alloy are shown in Figure 2. Figure 2 As shown: (a) iron 2p orbital; (b) cobalt 2p orbital; (c) chromium 2p orbital; (d) nickel 2p orbital; (e) aluminum 2p orbital; (f) copper 2p orbital. Figure 2 (a) shows that Fe 2+ , Fe 3+ The peak intensity is significantly higher than that of cast HEA, among which Fe 2+ , Fe 3+ 2p 3 / 2 The peak binding energies shifted from 709.53 eV and 711.61 eV to 709.73 eV and 711.97 eV respectively, and Fe 2+ , Fe 3+ The ratio increased from 0.69 in the cast state to 0.86, indicating that part of the Fe was oxidized during the spraying process, and the generation of high-valent Fe was conducive to the adsorption of the intermediate products of the HER reaction. Figure 2 From (b) in the figure, we can see that Co 2+ 、Co 3+ 2p 3 / 2 The binding energy moves from 782.78eV, 780.71eV to 780.10eV, 784.04eV, where Co 2+ The ratio of Co increases from 0.15 in the cast state to 0.21 in the reaction process. 2+ There is a large amount of free electrons that can be converted into Co 3+ Promote the reaction. Figure 2From (d) in the figure, we can see that the binding energy shifted from 872.24eV and 875.70eV to 873.63eV and 877.59eV, which proves that it was oxidized to a higher valence state during the spraying process. However, since the Ni element itself has good high temperature performance, Ni 2+ 、Ni 3+ The proportion of Figure 2 From (c) in the figure, we can see that Cr 3+ The percentage increased from 0.88 to 0.9, with little change because the Cr element is highly active and generates more oxidized states in the cast state. 0 With Cr 3+ The shift to a lower binding energy indicates an electron-rich state. Figure 2 (f) shows that due to the segregation of Cu element in the coating, Cu 2+ The presence of Cu element can provide good conductivity and more free electrons for the reaction. Figure 2 From (e) in the figure, we know that Al 0 The complete disappearance is due to the high affinity of Al and O, which is consistent with the EDS analysis results. The presence of transition metal oxides in the coating can provide more vacant oxygen; Figure 2 As shown in (d), the O1s spectrum has three characteristic peaks, corresponding to metal oxides (MO), defect / vacancy oxygen, hydroxyl or surface adsorbed oxygen. Compared with the cast HEA, the metal oxide (MO) peak in the FeCoCrNiAlCu HEA coating is significantly enhanced, with the proportion increasing from 0.06 to 0.25. The increase in metal oxides can increase the presence of vacancy oxygen, and more vacancy oxygen helps to reduce the overpotential of the OER reaction.
[0039] Electrochemical measurements
[0040] The high entropy alloys and HEA coatings of Example 1, Comparative Examples 1 and Comparative Examples 2 were respectively placed in 0.5MH2SO4 (PH = 0.3) electrolyte, and HER and OER tests were performed on a CHI660E electrochemical workstation using a standard three-electrode system with the HEA coating as the working electrode, the saturated calomel electrode as the reference electrode, and the carbon rod as the counter electrode. The immersion area of the HEA coating in the electrolyte was 0.5 cm -2 The HER was measured using linear voltammetry with a scan rate of 5 mV s -1 . Select 2mV s -1The OER data were obtained by scanning at a rate of 100 nm. All IR compensation values were 95%, and the tafel slope was calculated by the relationship between the potential and the current density (logarithm) of the LSV curve, with the formula η=b×logj+a. The electrochemical impedance spectroscopy measurement points were in the frequency range of 0.01Hz to 100kHz. The electrochemically active surface area (ECSA) of the coating was determined by double layer capacitance (Cdl). All measured potentials were converted into reversible hydrogen potentials, with the formula E(RHE)=E(SCE)+0.059×pH+0.2412V.
[0041] The OER test performance of the prepared FeCoCrNiAlCu HEA coating is shown in Figure 3 As shown: (a) LSV curve of oxygen evolution reaction; (b) Tafel plot; (c) double layer capacitance of oxygen evolution reaction. Figure 3 From (a) in the figure, we can see that the oxygen evolution reaction occurs at a current density of 10 mA cm -2 Under the condition of , the overpotential of FeCoCrNiAlCu HEA coating catalyst is (270mV), FeCoCrNiAl (300mV), FeCoCrNiCu (303mV). Figure 3 From (b) in Fig. 1, it can be seen that the Tafel slope of the FeCoCrNiAlCu HEA coating is (76.68 mV / dec -1 ), which is less than FeCoCrNiAl (201.97mV / dec -1 )、FeCoCrNiCu(157.17mV / dec -1 ), indicating that the FeCoCrNiAlCu HEA coating has a faster response speed in the OER reaction. Figure 3 From (c) in Fig. 1, it can be seen that the FeCoCrNiAlCuHEA coating has the highest C dl Value (7.58mF cm -2 ) indicates that it has the largest active specific surface area compared to other ingredients.
[0042] The HER test performance of the prepared FeCoCrNiAlCu HEA coating is as follows Figure 4 As shown: (a) LSV curve of hydrogen evolution reaction; (b) Tafel plot; (c) double layer capacitance of hydrogen evolution reaction; (d) Nyquist plot; (e) stability test of hydrogen evolution reaction; (f) LSV curve of overall water decomposition. Figure 4 (a) shows that when the current density is 10 mA cm -2 The overpotential of FeCoCrNiAlCu HEA coated catalyst is (99.3mV), which is lower than that of cast FeCoCrNiAlCu (134mV), FeCoCrNiAl (118mV), and FeCoCrNiCu (121mV). Figure 4 (b) shows that compared with other samples FeCoCrNiAlCu as-cast (98.4mV / dec -1 )、FeCoCrNiAl(74.72mV / dec -1 )、FeCoCrNiCu(69.71mV / dec -1 ), the FeCoCrNiAlCu HEA coating has the lowest Tafel slope (55.8 mV / dec -1 ) is similar to the commercial Pt / C electrode. According to the Tafel slope diagram, the reaction mechanism of HEA coating under acidic conditions is Volmer-Heyrosky, and the reaction rate determining step is Volemer. The morphology of the coating after the reaction is as follows Figure 5 As shown in (a), rice-like precipitates appear near the surface pores and the coating surface is etched during the reaction, further increasing the contact area between the solution and the workpiece. The results show that the pores in the coating and the synergistic effect of multiple elements promote the reaction and improve the catalytic kinetics of the catalyst. Figure 4 As shown in (c), the FeCoCrNiAlCu HEA coating (2.4 mF cm -2 ) is much smaller than that of other prepared samples, but it has the lowest overpotential, indicating that it has higher intrinsic active sites. Figure 4 As shown in (d), compared with the other components, the FeCoCrNiAlCu HEA coating has the smallest equivalent resistance (1.597Ω), indicating that it has a small electron transfer resistance and a faster electron transfer speed during the reaction. Stability is an important reference factor in acidic reactions. In order to determine the stability of the FeCoCrNiAlCu HEA coating sample in the HER reaction under acidic conditions, 3000 cycles of CV were performed in the working range. Figure 4 From (e) in the figure, it can be seen that the reaction overpotential decreases slightly after 1000 cycles, which may be because the coating surface and pores are further etched with the progress of the cycle to increase the reaction sites and promote the reaction. After 2000 cycles and 3000 cycles, the overpotential fluctuation is small, indicating that the FeCoCrNiAlCu HEA coating has good reaction stability in acidic electrolyte. Figure 4 From (f) in the figure, we can see that at 10 mA cm -2 The FeCoCrNiAlCu HEA coating (1.47 V) has a lower potential requirement than FeCoCrNiCu (1.58 V), showing good overall water electrolysis performance.
[0043] After the HER stability test, the structural characteristics of the FeCoCrNiAlCu HEA coating catalyst were detected. The scanning electron microscope image and energy spectrum scattering XPS spectrum of the prepared FeCoCrNiAlCu HEA coating after cycling are shown in Figure 2. Figure 5 Shown: (a) SEM image of FeCoCrNiAlCu HEA coating after cycling; (b) Iron 2p. Orbital XPS spectrum of FeCoCrNiAlCu HEA coating after cycling; (c) Cobalt 2p. Orbital XPS spectrum of FeCoCrNiAlCu HEA coating after cycling; (d) Chromium 2p. Orbital XPS spectrum of FeCoCrNiAlCu HEA coating after cycling; (e) Nickel 2p. Orbital XPS spectrum of FeCoCrNiAlCu HEA coating after cycling; (f) Aluminum 2p. Orbital XPS spectrum of FeCoCrNiAlCu HEA coating after cycling; (g) Copper 2p. Orbital XPS spectrum of FeCoCrNiAlCu HEA coating after cycling. Figure 5 As shown in (b), in the Fe 2p spectrum, Fe 2+ , Fe 3+ The binding energy increased from 709.73 eV and 711.79 eV to 711.09 eV and 714.32 eV, respectively, indicating that the Fe 0 The existence of may be because it is covered by the reactants and does not participate in the reaction further. Figure 5 From (c) and (e), we can see that Co and Ni have similar trends to Fe. 0 Completely disappeared 2+ With Co 3+ The increase in the ratio indicates that the reaction process of Co and Co 2+ Contributes a large number of free electrons to promote the reaction. Figure 5 As shown in (d), the Cr spectrum after stability test 0 It completely disappeared, indicating that Cr contributed some electrons in the reaction, but Cr 3+ There is no obvious change in the overall peak. Figure 5 As shown in (f), the Al spectrum is similar to that of Cr. 0 It completely disappears during the reaction, and Al 3+ The binding energy slightly shifts to the right from 74.56eV to 74.65eV. The above results show that Al and Cr are good stabilizing elements in the catalytic reaction of FeCoCrNiAlCu HEA coating. Figure 5 As shown in (g), in the Cu spectrum, the surface is covered by Cu precipitation products. 2+The peak intensity increased significantly, and the binding energy increased from 932.68 eV to 933.12 eV, indicating that Cu contributed a large number of electrons to be oxidized to a higher valence state during the reaction.
[0044] In summary, the FeCoCrNiAlCu HEA coating prepared in the present invention has excellent bifunctional catalytic ability and exhibits good hydrogen evolution (HER) and oxygen evolution (OER) catalytic performance in 0.5M H2SO4 electrolyte.
[0045] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution, characterized in that: The following steps are involved: S1. Take Fe, Co, Cr, Ni, Al and Cu single metals with a purity higher than 99.9% in a molar ratio of 1:1:1:1:1:1, clean and remove oil and impurities on the surface of each metal raw material, rinse with alcohol and blow dry for later use; S2, placing the metal raw materials into an electric arc furnace to melt into a FeCoCrNiAlCu high entropy alloy; S3, using a vacuum gas atomization device to process the FeCoCrNiAlCu high entropy alloy into FeCoCrNiAlCu high entropy alloy powder for spraying; S4. Clean the substrate surface before spraying and perform sandblasting on the substrate surface to increase the surface roughness of the substrate; S5. Use plasma spraying equipment to spray FeCoCrNiAlCu high entropy alloy powder on the surface of the substrate to prepare HEA coating. The main parameters of the spraying are: working voltage: 42V, working current: 600A, and argon gas flow rate 45L / min.
2. The method for preparing a high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution according to claim 1, characterized in that: The main parameters of the vacuum gas atomization device are: gas atomization of 5.0 MPa, heating power of 30 kW, feed speed of 0.05 mm / s, and alloy powder with a particle size of 14-45 μm is screened for spraying.
3. The method for preparing a high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution according to claim 1, characterized in that: The substrate is a Q235 steel plate.
4. The method for preparing a high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution according to claim 1, characterized in that: The sandblasting material used in the sandblasting process is white corundum Al2O3.
5. The method for preparing a high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution according to claim 1, characterized in that: The spraying thickness of the HEA coating is 400 μm.
6. A high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution prepared by the method according to any one of claims 1 to 5.
7. Use of the high entropy alloy coating having dual catalytic performance of hydrogen and oxygen evolution as claimed in claim 6 as a dual catalyst for hydrogen and oxygen evolution in water electrolysis.
Citation Information
Patent Citations
Preparation method of self-supporting high-entropy alloy electrode for electrolytic hydrogen production
CN113265675A
Alkaline electrolysis water membrane electrode assembly and preparation method thereof
CN117867550A
Method for preparing electrolyzed water oxygen evolution electrode based on laser fusion welding process
CN118497799A